2009
DOI: 10.1177/0146167209335461
|View full text |Cite
|
Sign up to set email alerts
|

On the Meaning and Measure of Narcissism

Abstract: For three decades, social-personality research on overt narcissism has relied almost exclusively on the Narcissistic Personality Inventory (NPI). However, the NPI suffers from a host of psychometric and validity concerns that make composite NPI scores (summed across its subscales) difficult to interpret. The present studies propose that narcissistic characteristics tend to fall under two general clusters: grandiosity and entitlement. The studies show that measures of grandiosity and entitlement interact to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
309
0
16

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(358 citation statements)
references
References 40 publications
21
309
0
16
Order By: Relevance
“…= 0.10) exceeded the recommended minimum value of 0.70, indicating high rater reliability. Consistent with much of the prior research on the relations between the Big Five and measures of grandiose narcissism, we found that ratings of CEO narcissism were significantly correlated with ratings of both extraversion (r = 0.50, p b 0.01) and agreeableness (r = − 0.83, p b 0.001) (Brown et al, 2009;Holtzman et al, 2010;Miller et al, 2011;Paulhus & Williams, 2002).…”
Section: Independent Variables 221 Ceo Narcissismsupporting
confidence: 86%
See 1 more Smart Citation
“…= 0.10) exceeded the recommended minimum value of 0.70, indicating high rater reliability. Consistent with much of the prior research on the relations between the Big Five and measures of grandiose narcissism, we found that ratings of CEO narcissism were significantly correlated with ratings of both extraversion (r = 0.50, p b 0.01) and agreeableness (r = − 0.83, p b 0.001) (Brown et al, 2009;Holtzman et al, 2010;Miller et al, 2011;Paulhus & Williams, 2002).…”
Section: Independent Variables 221 Ceo Narcissismsupporting
confidence: 86%
“…Although these two forms of narcissism may be conflated in some overall measures of trait narcissism, they do reflect distinct nomological networks. In terms of the Big 5 personality dimensions, grandiose narcissism is associated with higher extraversion and lower agreeableness while vulnerable narcissism is related to various facets of neuroticism including anxiety, self-consciousness, and depression as well as relatively low levels of self-esteem (Brown, Budzek, & Tamborski, 2009;Miller et al, 2011;Holtzman, Vazire, & Mehl, 2010;Paulhus & Williams, 2002). Interestingly, so-called "thin slice" measures, in which there is a very brief observation of a person, show that individuals who are high on measures of grandiose narcissism are perceived by others as narcissistic while those who are high on vulnerable narcissism are not (Miller et al, 2011).…”
Section: Narcissism Qualities and Dimensionsmentioning
confidence: 99%
“…Both groups accentuate an essential core of narcissism, as well as moderation in its expression as a function of underlying temperament [1] or personality [2]. We refer to the core here as entitlement as others have before us [38,39], and refer to the two moderating dimensions as exhibitionism and vulnerability. Krizan and Herlache link exhibitionism and vulnerability to approach and avoidance systems, whereas Miller and colleagues, operating from the framework of the Big Five personality traits, link these to extraversion and neuroticism.…”
Section: Rapprochement: Structural Integrationmentioning
confidence: 99%
“…Individuals with excessively narcissistic traits tend to show a strong sense of self-importance (Brown, Budzek & Tamborski, 2009), or a strong sense of entitlement, characterized by a general feeling that they deserve more rewards and recognition than others (Campbell et al 2004), see themselves more positively than their peers (Robins & Beer, 2001), and believe they are better than others and strongly depend on positive feedback from others (Rhodewalt & Morf, 1998). If this feedback is not obtained, such as in the case of failure, the narcissist responds with extreme expressions of negative emotions (Bushman & Baumeister, 1998;Rhodewalt & Morf, 1998).…”
Section: O Objetivo Dessa Pesquisa Foi Identificar Se Traços Não Patomentioning
confidence: 99%